2009
DOI: 10.1080/09658210903107846
|View full text |Cite
|
Sign up to set email alerts
|

Why people rehearse their memories: Frequency of use and relations to the intensity of emotions associated with autobiographical memories

Abstract: People may choose to rehearse their autobiographical memories in silence or to disclose their memories with other people. This paper focuses on five types of memory rehearsal: involuntary rehearsal, rehearsal to maintain an event memory, rehearsal to re-experience the emotion of an event, rehearsal to understand an event, or rehearsal for social communication. A total of 337 participants recalled event memories, provided estimates of how often each event was rehearsed and for what reason, and rated the affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 46 publications
(62 reference statements)
3
60
1
1
Order By: Relevance
“…Walker et al, (2009) found that positive events tend to be more rehearsed than negative events, across different types of rehearsal. They also found rehearsal to be generally negatively related to the fading of emotional intensity.…”
Section: Effects Of Emotional Valence On the Long-term Accessibility mentioning
confidence: 91%
“…Walker et al, (2009) found that positive events tend to be more rehearsed than negative events, across different types of rehearsal. They also found rehearsal to be generally negatively related to the fading of emotional intensity.…”
Section: Effects Of Emotional Valence On the Long-term Accessibility mentioning
confidence: 91%
“…Involuntary memories are typically sensory-perceptual rather than verbal (Arntz, de Groot, & Kindt, 2005; Brewer, 1996; Conway, 1990, 2005; Conway, Meares, & Standart, 2004; Conway & Pleydell-Pearce, 2000), relate to specific events rather than summaries across several events (Schlagman & Kvavilashvili, 2008) and are more frequently negative than positive (Bywaters, Andrade, & Turpin, 2004; Walker, Skowronski, Gibbons, Vogl, & Ritchie, 2009). However, laboratory research in experimental psychology has predominately focussed on memories associated with deliberate, intentional recollection.…”
Section: Introductionmentioning
confidence: 99%
“…As Cason (1932) observed, at event recall, the intensity of positive affect (PA) prompted by recalling positive life events typically exceeds the intensity of negative affect (NA) prompted by recalling negative life events. This outcome, in part, reflects the fading affect bias (FAB; Gibbons, Lee, & Walker, 2011;Landau & Gunter, 2009;Walker, Skowronski, Gibbons, Vogl, & Ritchie, 2009;Walker, Skowronski, & Thompson, 2003;Walker, Vogl, & Thompson, 1997): NA generally fades faster from event occurrence to event recall than PA.…”
mentioning
confidence: 96%